1998
DOI: 10.1210/endo.139.9.6201
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Affects Pancreatic Endocrine Functions through the Sympathetic Nervous System1

Abstract: The effects of leptin on the secretion of insulin and glucagon were examined. In an experiment involving insulin response to an iv glucose load in vagotomized rats, the plasma concentrations of insulin were significantly lower in the leptin (20 nmol/kg BW)-treated group than in a control group. However, in intact rats and rats that had undergone both vagotomy and chemical sympathectomy, this suppressive effect of leptin on insulin secretion was not detected. In an experiment involving a hypoglycemia-induced gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…The initial evidence came from a study showing that leptin increased norepinephrine turnover in BAT (12), and was followed by studies mapping the neural pathways within the sympathetic nervous system activated by leptin (13)(14)(15). Subsequent studies have shown that surgical (16), chemical (17,39), or genetic (18) sympathectomy blocked leptin's effects on gene expression in both BAT and WAT. The latter studies established a requirement for the long form of the leptin receptor (Ob-Rb), but did not distinguish between central versus peripheral sites of action for leptin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial evidence came from a study showing that leptin increased norepinephrine turnover in BAT (12), and was followed by studies mapping the neural pathways within the sympathetic nervous system activated by leptin (13)(14)(15). Subsequent studies have shown that surgical (16), chemical (17,39), or genetic (18) sympathectomy blocked leptin's effects on gene expression in both BAT and WAT. The latter studies established a requirement for the long form of the leptin receptor (Ob-Rb), but did not distinguish between central versus peripheral sites of action for leptin.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted, however, that although supraphysiologic levels of leptin are capable of producing significant direct effects on adipose tissue (10,11), increments of plasma leptin in the physiological range are thought to act primarily through receptors in the hypothalamus (10). Occupancy of hypothalamic leptin receptors promotes activation of the sympathetic nervous system (12)(13)(14)(15), and recent studies using surgical (16), chemical (17), and transgenic approaches (18) have shown that norepinephrine is required for leptin effects on gene expression in both brown and white adipose tissue (19 -22). Thus, several lines of evidence support an emerging consensus that norepinephrine represents the peripheral signal linking hypothalamic leptin receptors to leptindependent changes in adipocyte gene expression.…”
mentioning
confidence: 99%
“…Leptin leads to increased FFA release from WAT possibly via a direct action on adipocytes [69] but much more importantly by increasing SNS activity [170,214] in the ARC [215]. This increased adipocyte lipolysis is also mediated by its direct [216] and SNS-induced [217] inhibitory effect on insulin secretion, demonstrated with changes in physiological concentrations [218].…”
Section: Leptinmentioning
confidence: 99%
“…Although many of the effects of leptin on the regulation of total body fat are due to the effects of this hormone on food intake, an increasing number of studies suggest that the actions of leptin on energy balance are due, at least in part, to activation of the sympathetic nervous system (SNS) and subsequent increases in metabolism [46,47]. Furthermore, stimulation of the leptin system increases sympathetic activity in a variety of peripheral tissues [47].…”
Section: The Autonomic Nervous Systemmentioning
confidence: 99%